Design Reuse Method of Corn Picking Device Based on Case-Based Reasoning - Rongjian Tai; Bin Li; Zhimin Sun; Qingjiang Li; Rongqing Liang; Bo Zhong (BioResources, 2023)
In order to shorten the design cycle of corn snapping mechanism, a case reuse design method of snapping devices based on user requirements was proposed. A matter-element model is used to build a case matter-element database and parametric model library together to form a case database; the case attributes are divided, the retrieval scope is narrowed through the matching of core parameters, and the similarity of matching parameters and performance evaluation parameters is calculated by using analytic hierarchy process and deviation maximization method to realize the retrieval of similar cases. The transformation relationship between the design requirements and the main driving parameters of the parametric model is established by using the rule association method to realize the case’s modification. The engineering discrete element method is used to simulate the reuse case, and an improved method is proposed according to the simulation results. The improved device is verified by simulation and field experiments. The results show that the operating performance of the improved snapping device is improved, and the feasibility and effectiveness of the design reuse method are verified, which can provide technical reference for the intelligent design of agricultural machinery and equipment.